Relative Frequency (Composition) of Anopheles sp. Mosquitoes as Malaria Vectors in Kulon Progo District Special Region of Yogyakarta - Wathon, Syubbanul; Senjarini, Kartika; Masruroh, Binti; Oktarianti, Rike; Rehmann, Holger (Jurnal Riset Biologi dan Aplikasinya, 2024)
Malaria is caused by Plasmodium infection transmitted Anopheles sp. One of the obstacles in malaria control is the variation of Anopheles sp. Species which have various characteristics and behaviour, so it’s very important to understand the species of Anopheles sp. with aim to develop the disease control program. This study was conducted in Kulon Progo Regency, Yogyakarta, one of the malaria endemic areas in Indonesia. Data collection of Anopheles sp. species diversity was carried out through landing collection inside and outside people’s homes at 18.00 - 06.00 WIB. Observations of abiotics factors in the habitat of Anopheles sp. larvae was carried out around the landing collection location. The result of research conducted in the Samigaluh, Kalibawang, and Pengasih Sub-Districts showed that the most common species found was Anopeheles vagus. The dominance of Anopheles vagus occurred in the Kalibawang and Pengasih dictricts, while in the Samigaluh Sub-Districts it became the second most among other species. Measurement of abiotic factors in the habitat of Anopheles sp. larvae through the parameters of temperature, air humidity, pH DO of water shows that the location where the larvae were found can support larval breeding and growth. That can be a factor in the large population of Anopheles sp., especially Anopheles vagus, which is a known vector of malarias based on research and its vectorial capacity.